2017
DOI: 10.1016/j.compgeo.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of uncertainty in bedrock depth and hydraulic properties on the stability of a variably-saturated slope

Abstract: a b s t r a c tWe investigate the uncertainty in bedrock depth and soil hydraulic parameters on the stability of a variably-saturated slope in Rio de Janeiro, Brazil. We couple Monte Carlo simulation of a threedimensional flow model with numerical limit analysis to calculate confidence intervals of the safety factor using a 22-day rainfall record. We evaluate the marginal and joint impact of bedrock depth and soil hydraulic uncertainty. The mean safety factor and its 95% confidence interval evolve rapidly in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
(135 reference statements)
1
15
0
6
Order By: Relevance
“…Moradi et al [6] found that bedrock topography would affect groundwater distribution and pore water pressure, and variable bedrock topography significantly affected slope stability. Gomes et al [7] evaluated the marginal and joint effects of uncertainty in bedrock depth and hydraulic characteristics using the Monte Carlo method, which significantly increased slope failure probability. rough a set of centrifugal experiments, Zhao et al [8] discovered that the failure modes were different due to the difference of inclination and roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Moradi et al [6] found that bedrock topography would affect groundwater distribution and pore water pressure, and variable bedrock topography significantly affected slope stability. Gomes et al [7] evaluated the marginal and joint effects of uncertainty in bedrock depth and hydraulic characteristics using the Monte Carlo method, which significantly increased slope failure probability. rough a set of centrifugal experiments, Zhao et al [8] discovered that the failure modes were different due to the difference of inclination and roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Estes elementos, em geral, possuem configuração triangular para problemas 2D. Exemplo de malha 3D utilizada em problemas de fluxo em solos não saturados é ilustrada em [ 3 ].Considera-se que apenas o valor da propriedade ψ é conhecido nos "nós". Assim, os valores dentro do elemento podem ser aproximados por uma interpolação entre os valores nodais.…”
Section: Soluções Numéricasunclassified
“…Nesse sentido, as PTF's no presente estudo buscam, a partir da distribuição do tamanho de partículas, fornecer seu respectivo conjunto de parâmetros hidráulicos. O PTF Rosetta [ 40 ] será utilizado e possui estrutura de funcionamento idêntica à apresentada por Gomes [ 3 ]. A partir de limites máximos e mínimos de conteúdos de areia (S), silte (Si) e argila (C) e um número w de combinações de dados são obtidos w respectivos conjuntos de parâmetros hidráulicos da seguinte forma: [ θ r , θ s , α, n, K…”
Section: Metodologia Para Calibrar O Modelo Da Epr Através Do Eimunclassified
See 2 more Smart Citations